Paul Ronzheimer, Sebastian Kurz. Die Biografie, Herder, Freiburg im Breisgau 2018, ss. 191. - Romejko, Adam (Studia Gdańskie, 2021)
Paul Ronzheimer, Sebastian Kurz. Die Biografie, Herder, Freiburg im Breisgau 2018, ss. 191.